Unveiling the efficiency of microwave-assisted hydrothermal treatment for the preparation of SrTiO3 mesocrystals - Da Silva, Luís F.; Catto, Ariadne C.; Avansi, Waldir; Mesquita, Alexandre [UNESP]; Maia, Lauro J. Q.; Lopes, Osmando F.; Li, Máximo Siu; Moreira, Mário L.; Longo, Elson; Andrés, Juan; Mastelaro, Valmor R. (My University, 2019)
Material processing has become essential for the proper control, tuning and consequent application of the properties of micro/nanoparticles. In this case, we report herein the capability of the microwave-assisted hydrothermal (MAH) method to prepare the SrTiO3 compound, as a case study of inorganic compounds. Analyses conducted by X-ray diffraction, X-ray photoelectron and X-ray absorption spectroscopies confirmed that the MAH route enables the formation of pristine SrTiO3. The results indicated that the combination of thermal and non-thermal effects during the MAH treatment provides ideal conditions for an efficient and rapid synthesis of pristine SrTiO3 mesocrystals. Scanning electron microscopy images revealed a cube-like morphology (of ca. 1 μm) formed via a self-assembly process, influenced by the MAH time. Additionally, photoluminescence measurements revealed a broad blue emission related to intrinsic defects, which decreased with the MAH synthesis time.